2022
DOI: 10.3892/etm.2022.11287
|View full text |Cite
|
Sign up to set email alerts
|

Sinensetin suppresses angiogenesis in liver cancer by targeting the VEGF/VEGFR2/AKT signaling pathway

Abstract: Sinensetin (SIN) is a polymethoxy flavone primarily present in citrus fruits. This compound has demonstrated anticancer activity. However, the underlying mechanism of its action has not been fully understood. The present study investigated the impact of SIN on angiogenesis in a liver cancer model. In a murine xenograft tumor model, SIN inhibited the growth of HepG2/C3A human liver hepatoma cell-derived tumors and reduced the expression levels of platelet/endothelial cell adhesion molecule-1 and VEGF. In HepG2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Otherwise, SNS would target p53-mediated AMPK/mTOR signaling to trigger autophagy and apoptosis of Hepatocellular Carcinoma Cells . SNS also inhibited VEGF/VEGFR2/AKT signaling to impaired angiogenesis in liver cancer . Thus, we and others showed that SNS possesses a protective role in lung and liver diseases.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Otherwise, SNS would target p53-mediated AMPK/mTOR signaling to trigger autophagy and apoptosis of Hepatocellular Carcinoma Cells . SNS also inhibited VEGF/VEGFR2/AKT signaling to impaired angiogenesis in liver cancer . Thus, we and others showed that SNS possesses a protective role in lung and liver diseases.…”
Section: Discussionmentioning
confidence: 89%
“…27 SNS also inhibited VEGF/VEGFR2/AKT signaling to impaired angiogenesis in liver cancer. 28 Thus, we and others showed that SNS possesses a protective role in lung and liver diseases. Accumulating evidence highlighted that macrophage was involved in and initiated the inflammatory injury.…”
Section: Discussionmentioning
confidence: 89%
“…Researchers have found that NBIF induces mitochondrial outer membrane protein Tom20 alteration through ROS both in vivo and in vitro, thereby enhancing Bax recruitment to mitochondria and activating the calpain I-GSDME pathway in liver cancer cells to induce pyroptosis. Sinensetin (SIN), a polymethoxylated flavone found in citrus fruits, inhibits angiogenesis in liver cancer by targeting the VEGF/VEGFR2/AKT signaling pathway in a murine xenograft tumor model [ 51 ]. Studies indicate that extramedullary hematopoiesis (EMH) is a crucial mechanism for myeloid-derived suppressor cells (MDSCs) accumulation in tumor tissues, contributing to disease progression.…”
Section: Nps With Therapeutic Activity For Liver Cancermentioning
confidence: 99%
“…The results revealed decreased expression of MMP2, MMP9, and VEGF in the rat liver, accompanied by increased levels of TIMP3 and miR-1-3p expression, suggesting that the anti-angiogenic effect of TQ in HCC is mediated through miR-1-3p regulation [ 116 ]. Natural polysaccharides like Asparagus polysaccharide, flavonoids like sinensetin, and polyphenols like tannins have also been found to exert anti-hepatocellular carcinoma effects by inhibiting tumor angiogenesis [ 51 , 106 , 128 ].…”
Section: The Main Action Pathway and Potential Mechanism Of Natural C...mentioning
confidence: 99%